Diagnosing Polyparasitism in a High-Prevalence Setting in Beira, Mozambique: Detection of Intestinal Parasites in Fecal Samples by Microscopy and Real-Time PCR. - Lynn Meurs; Anton M Polderman; Natalie V S Vinkeles Melchers; Eric A T Brienen; Jaco J Verweij; Bernhard Groosjohan; Felisberto Mendes; Manito Mechendura; Dagmar H Hepp; Marijke C C Langenberg; Rosanne Edelenbosch; Katja Polman; et al. (Public Library of Science (PLoS), 2017)
BACKGROUND:Many different intestinal parasite species can co-occur in the same population. However, classic diagnostic tools can only frame a particular group of intestinal parasite species. Hence, one or two tests do not suffice to provide a complete picture of infecting parasite species in a given population. The present study investigated intestinal parasitic infections in Beira, Mozambique, i.e. in the informal settlement of Inhamudima. Diagnostic accuracy of five classical microscopy techniques and real-time PCR for the detection of a broad spectrum of parasites was compared. METHODOLOGY/PRINCIPAL FINDINGS:A cross-sectional population-based survey was performed. One stool sample per participant (n = 303) was examined by direct smear, formal-ether concentration (FEC), Kato smear, Baermann method, coproculture and real-time PCR. We found that virtually all people (96%) harbored at least one helminth, and that almost half (49%) harbored three helminths or more. Remarkably, Strongyloides stercoralis infections were widespread with a prevalence of 48%, and Ancylostoma spp. prevalence was higher than that of Necator americanus (25% versus 15%), the hookworm species that is often assumed to prevail in East-Africa. Among the microscopic techniques, FEC was able to detect the broadest spectrum of parasite species. However, FEC also missed a considerable number of infections, notably S. stercoralis, Schistosoma mansoni and G. intestinalis. PCR outperformed microscopy in terms of sensitivity and range of parasite species detected. CONCLUSIONS/SIGNIFICANCE:We showed intestinal parasites-especially helminths-to be omnipresent in Inhamudima, Beira. However, it is a challenge to achieve high diagnostic sensitivity for all species. Classical techniques such as FEC are useful for the detection of some intestinal helminth species, but they lack sensitivity for other parasite species. PCR can detect intestinal parasites more accurately but is generally not feasible in resource-poor settings, at least not in peripheral labs. Hence, there is a need for a more field-friendly, sensitive approach for on-the-spot diagnosis of parasitic infections.